Validity and score interpretation of the 12-item Psoriatic Arthritis Impact of Disease: an analysis of pooled data from two phase 3 trials of bimekizumab in patients with psoriatic arthritis - Laure Gossec; Ana-Maria Orbai; Maarten de Wit; Dafna D Gladman; Laura C Coates; Alexis Ogdie; Vanessa Taieb; Jeremy Lambert; Barbara Ink; Christopher G Pelligra; Valérie Ciaravino (RMD Open)
Objectives To investigate psychometric performance of the 12-item Psoriatic Arthritis Impact of Disease (PsAID-12) total and individual item scores in patients with psoriatic arthritis (PsA) and to estimate score change thresholds and scores corresponding to different levels of symptom/impact severity.Methods Data up to week 16 from 1252 patients with active PsA enrolled in two randomised controlled trials of bimekizumab (BE OPTIMAL (NCT03895203) and BE COMPLETE (NCT03896581)) were used to assess construct validity (correlations with other patient-reported outcomes), known-groups validity (based on Minimal Disease Activity index, Disease Activity Index for Psoriatic Arthritis and Psoriatic Arthritis Disease Activity Score), reliability (Cronbach’s alpha and intraclass correlation coefficients (ICCs)) and responsiveness (sensitivity to change). Clinically meaningful within-patient improvement thresholds were estimated by anchor-based and distribution-based analyses, and symptom/impact severity thresholds were estimated by receiver operating characteristic curve analyses.Results The mean (SD) PsAID-12 total score at baseline was 4.19 (1.94). PsAID-12 scores demonstrated good convergent validity and good known-groups validity. Internal consistency reliability (Cronbach’s alpha 0.95) and test–retest reliability (ICC ≥ 0.70) were also good. Responsiveness was acceptable (correlations ≥0.30 for most scores). Improvement thresholds were estimated at 1.5–2 points for the PsAID-12 total score and 2 or 3 points for item scores. Thresholds for different levels of symptom/impact severity could be derived for most PsAID-12 items.Conclusions The PsAID-12 demonstrated robust psychometric properties in a large sample of patients with active PsA, supporting its use as a fit-for-purpose patient-reported outcome in this population. Furthermore, thresholds for score interpretation were derived.